2006
DOI: 10.2478/v10001-006-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Reaction to Work in Cold Microclimate

Abstract: Objectives: In Poland, occupational exposure to cold microclimate is quite common (5.1 workers/1000 occupationally active people). Reports on health effects of this exposure are rather scarce. The aim of the study was to evaluate the physiological reaction in workers occupationally exposed to cold microclimate. Materials and Methods: Examinations were performed in a group of 102 workers (41 women and 61 men) employed at cold storage units. The mean age in the group was 39.1 ± 9.9 years and the duration of empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…Long-term occupational exposure to cold environment increases blood pressure in male workers working in cold areas more than once per day 79) . Bortkiewicz et al 34) also found higher blood pressure in workers with exposure to ambient temperatures varying from 0 to 10˚C for 8 h/d than in workers with exposure to ambient temperatures between 10˚C and 14˚C for 8 h/d. However, the chronic effect of occupational exposure to a cold microclimate on HRV was not significant, indicating that HRV might not be a sensitive marker for capturing the adverse effects of exposure to a cold environment on the cardiovascular system.…”
Section: Cold Environmentmentioning
confidence: 91%
See 1 more Smart Citation
“…Long-term occupational exposure to cold environment increases blood pressure in male workers working in cold areas more than once per day 79) . Bortkiewicz et al 34) also found higher blood pressure in workers with exposure to ambient temperatures varying from 0 to 10˚C for 8 h/d than in workers with exposure to ambient temperatures between 10˚C and 14˚C for 8 h/d. However, the chronic effect of occupational exposure to a cold microclimate on HRV was not significant, indicating that HRV might not be a sensitive marker for capturing the adverse effects of exposure to a cold environment on the cardiovascular system.…”
Section: Cold Environmentmentioning
confidence: 91%
“…Any selected HRV parameters (SDNN and HF, LF, and VLF components) during rest in the morning did not differ between workers who were chronically exposed to different microclimate conditions (-26 to 20˚C) 34) .…”
Section: Cold Environmentmentioning
confidence: 99%
“…Because of the computer databases used for the health data, we were not able to consider all of the risk factors for the CVD, like smoking status, alcohol consumption, obesity, physical activity and socioeconomic status. Because of the age specific results in this study, with the vision of defining the most vulnerable population, it might have been advisable to define more than 2 age groups (e.g., 25-35 years old, 36-55 years old, or > 80 years old) as well as gender specific groups according to the results of some other authors [33]. The use of the hospital admissions as health data does not represent the real state of morbidity, too because some cases were linked only to medical examination, without admission.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences between the different categories of working temperatures were observed. The large variation in metabolic rate was due to significant differences between work shift durations, varying from approximately 5 to 18 h (Bortkiewicz et al 2006). In the study of Kluth et al (2012), HR rose above the resting level in senior workers (aged 40-65 years) by ϳ30 beats·min −1 and in younger workers (aged 20-35 years) by ϳ35 beats·min −1 .…”
Section: Food Processingmentioning
confidence: 99%